Method for producing porous material

By using bio-based polymers and polysaccharides with hydroxy acid groups to form a gel with polyvalent metal ions, and producing porous materials through a specific drying process, the problems of material instability and difficulty in loading and releasing active agents in the prior art are solved, and high stability and efficient loading of released porous materials are achieved.

JP2025508099APending Publication Date: 2025-03-21AIRGEL-IT GMBH
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2024553626
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-08
Filing Date
2023-03-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, porous materials used often involve harmful substances and require chemical crosslinking or hydrophobization steps, resulting in unstable materials and difficult to load and release active agents.

Method used

Porous material is made by providing a mixture of bio-based polymers and polysaccharides with hydroxy acid groups and contacting them with an aqueous solution of polyvalent metal ions to form a gel, then exposing the gel to a water-miscible solvent, and finally by supercritical drying or other drying methods.

Benefits of technology

A stable porous material is achieved from harmless aqueous solutions, which hardly shrink under typical environmental conditions and can effectively load and release liquids or liquefied organic solvents or oils without chemical crosslinking or hydrophobization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025508099000001
    Figure 2025508099000001
  • Figure 2025508099000002
    Figure 2025508099000002
  • Figure 2025508099000003
    Figure 2025508099000003
Patent Text Reader

Abstract

The present invention relates to a method for preparing a porous material, comprising the steps of providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2) and water, contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A), exposing the gel (A) obtained to a water-miscible solvent (L) to obtain a gel (B) and drying the gel (B). The present invention further relates to the porous material thus obtained and the use of this porous material as thermal insulation, as a support material for the loading and release of active agents, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in household appliances, in building and construction applications, in domestic and commercial electrical appliance applications, in temperature control logistics applications, in vacuum insulation applications, in batteries, in clothing applications, in food applications, in cosmetics applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications or as a support material or adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for preparing a porous material, comprising the steps of providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2) and water, contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A), exposing the gel (A) obtained to a water-miscible solvent (L) to obtain a gel (B) and drying the gel (B). The present invention further relates to the porous material thus obtained and the use of this porous material as thermal insulation, as a support material for the loading and release of active agents, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in household appliances, in building and construction applications, in domestic and commercial electrical appliance applications, in temperature control logistics applications, in vacuum insulation applications, in batteries, in clothing applications, in food applications, in cosmetics applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications or as a support material or adsorbent.

[0002] Porous materials based on organic polymers, such as polymer foams, with pore sizes in the range of a few microns or less and high porosities of at least 70% are particularly suitable for a variety of applications.

[0003] Such porous materials with small average pore size can be in the form of organic aerogels or xerogels, for example, produced by a sol-gel process and then dried. In the sol-gel process, a sol based on an organic gel precursor is first produced, which is then gelled to form a gel by a crosslinking step. To obtain a porous material, for example an aerogel, from the gel, the liquid must be removed. In the following, this step will be referred to as drying for simplicity.

[0004] The present invention relates to a method for making a porous material containing a bio-based polymer and a polysaccharide having carboxylic acid groups, and to such a porous material and methods of use thereof.

[0005] In the context of the present invention, bio-based polymers are understood to be polymers obtained from renewable resources (algae, bacteria, microorganisms, plants, etc.). Bio-based polymers can be obtained mainly in two different ways: direct production of the polymer or production of bio-based monomers and their further (bio)chemical polymerization. Direct production of biopolymers can be achieved by microorganisms (polyhydroxyalkanoates, PHA), algae (alginates, etc.), superior plants (pectins, etc.) or by several producers, for example cellulose is produced by superior plants but also by bacteria, chitosan is produced by crustaceans but also by fungi.

[0006] In particular, the present invention relates to a method for producing protein, lignin, tannin, cellulose, silica and / or alginate-containing porous materials. Lignin is a heterogeneous biopolymer. Depending on its origin, e.g. wood or plant source, and extraction method, properties such as molar mass or degree of condensation, and chemical composition may differ. Typically, lignin is a disordered biopolymer with three main building blocks, namely coumaryl alcohol, coniferyl alcohol and sinapyl alcohol. Other suitable bio-based polymers are, for example, tannins. Tannins may be natural products found in bark and other biological sources. There are several classes of tannins, generally differing in base or monomer units.

[0007] In principle, porous materials based on organic polymers, preferably bio-based polymers, are known in the art, for example based on polysaccharides, polypeptides, polyphenols, such as cellulose, gelatin and lignin, or mixtures of bio-based polymers. Methods for the preparation of lignin-based aerogels are also known in the art.

[0008] Several processes have been disclosed in the scientific literature. For example, an article in the Journal of Supercritical Fluids, 2015, 105, 1-8, describes a process for the preparation of hybrid alginate and lignin aerogels using pressurized carbon dioxide for gelation. When an alkaline aqueous solution of alginate and lignin containing calcium carbonate was exposed to CO2, a hydrogel was formed.

[0009] US02010329208A1 discloses a method for producing high-purity lignin-based carbon aerogel.

[0010] Highly porous organic aerogels based on tannin and lignin are disclosed in "New Tannin-Lignin Aerogels", Grishechko, L. et al., Industrial Crops and Products, 2013, 41, 347-355. The hydrogels described are prepared at constant solids content and constant pH, but with different mass ratios of tannin / lignin and (tannin+lignin) / formaldehyde.

[0011] Generally, organic molecules such as isocyanates or aldehydes are used as crosslinking agents. In many applications, these compounds are disadvantageous because they are often hazardous and may remain in trace amounts in the resulting material.

[0012] Also known in the art are alginate-based porous materials. In particular, a method for producing alginate-based polysaccharide foams is known from WO 94 / 00512. Also, in the scientific literature, for example Partap et al. (2006, "Supercritical Carbon Dioxide in Water" Emulsion-Templated Synthesis of Porous Calcium Alginate Hydrogels. Advanced Materials 18, 501-504), a gelation process induced by pressurized CO2 in alginate-based systems is disclosed.

[0013] Due to their porosity and stability, aerogels or xerogels are also used as adsorbents or carrier materials. For example, WO2016032733A2 describes non-dusting biopolymer aerogels for loading liquid active substances, but the loading is carried out using a supercritical medium using high pressure and high temperature. WO2019167013A1 describes highly water-absorbent polysaccharide biopolymer aerogels, but requires chemical cross-linking.

[0014] EP3741794A1 describes an aerogel / hydrogel composite for loading and releasing oils or moisture such as perfumes, but uses dusty silica aerogel which needs to be hydrophobized.EP2663395B1 describes an aerogel / hydrogel composite for loading and releasing drugs, but uses dusty silica aerogel which needs to be hydrophobized.

[0015] CN114958480A describes silica aerogel as a carrier for fragrances, but the material is dusty and requires hydrophobization. WO2018056652A describes silica aerogel as a carrier for UV-blocking agents to prevent skin irritation, but the silica aerogel is dusty. WO2017023702A1 describes silica aerogel / polymer resin as a fragrance releasing material, but the silica aerogel is dusty and is known to require hydrophobization. Budtova et al. (Cellulose 2019,26,81-121(10.1007 / s10570-018-2189-1)) describes cellulose aerogel for uptake of oils or organic solvents, but requires chemical cross-linking and / or hydrophobization.

[0016] CN105601983B describes polysaccharide biopolymer materials based on freeze-drying as aroma carriers, but chemical cross-linking is required. WO2019190379A1 describes hybrid aerogels of cellulose and electrostatically charged polysaccharides, but gelation requires energy from heating.

[0017] The use of aerogels in pharmaceutical applications is disclosed, for example, in WO96 / 25950 A1, WO9501165A1, WO2009062975A1 or WO02051389A2.

[0018] The materials disclosed in this art are either dust-like and often based on silica that requires hydrophobization, based on chemically cross-linked biopolymers, or require energy input for loading and heating in the preparation process. [Prior art documents] [Patent documents]

[0019] [Patent Document 1] US02010329208A1 [Patent Document 2] WO 94 / 00512 [Patent Document 3] WO2016032733A2 [Patent Document 4] WO2019167013A1 [Patent Document 5] EP3741794A1 [Patent Document 6] EP2663395B1 [Patent Document 7] CN114958480A [Patent Document 8] WO2018056652A [Patent Document 9] WO2017023702A1 [Patent Document 10] CN105601983B [Patent Document 11] WO2019190379A1 [Patent Document 12] WO96 / 25950 A1 [Patent Document 13] WO9501165A1 [Patent Document 14] WO2009062975A1 [Patent Document 15] WO02051389A2 [Non-patent literature]

[0020] [Non-Patent Document 1] Journal of Supercritical Fluids,2015,105,1-8 [Non-Patent Document 2] "New Tannin-Lignin Aerogels", Grishechko, L. et al., Industrial Crops and Products, 2013, 41, 347-355 [Non-Patent Document 3] Partap et al., 2006, “Supercritical Carbon Dioxide in Water” Emulsion-Templated Synthesis of Porous Calcium Alginate Hydrogels.Advanced Materials 18,501-504 [Non-Patent Document 4] Budtova et al., Cellulose 2019, 26, 81-121 (10.1007 / s10570-018-2189-1) Summary of the Invention [Problem to be solved by the invention]

[0021] The object of the present invention was to avoid the above-mentioned drawbacks. One object of the present invention was to provide a method for preparing a porous material based on a bio-based polymer, which avoids harmful substances. A further object of the present invention was to provide a porous material suitable for use as insulation or as a core for vacuum insulation, or for battery applications, for electrode materials in batteries, fuel cells or electrolysis, for catalysis, for capacitors, or for cosmetic, pharmaceutical or agricultural applications. Furthermore, the object of the present invention was to provide a method for preparing a porous material from a bio-based polymer, which is stable and can be used as an adsorbent or carrier material, preferably also suitable for releasing adsorbed liquids.

[0022] It was a further object of the present invention to provide a porous material which can be prepared from non-hazardous aqueous solutions, exhibits little shrinkage when exposed to typical ambient conditions for storage stability, and can be loaded with liquid or liquefied organic solvents or oils. [Means for solving the problem]

[0023] According to the invention, this object is achieved by at least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); The problem is solved by a method for preparing a porous material, comprising: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] According to a further embodiment, the present invention relates to a method for producing a pharmaceutical composition comprising at least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from water-soluble bio-based polymers and inorganic precursors, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); The present invention also relates to a method for preparing a porous material, comprising:

[0025] According to the invention, bio-based polymers and polyionic biopolymers are used to form the gel. Suitable bio-based polymers and polyionic biopolymers are in principle known from the art. Preferably, polyanionic biopolymers are used as polyionic biopolymers. Suitable ionic biopolymers are, for example, polysaccharides, in particular polysaccharides with carboxylic acid groups.

[0026] According to the present invention, preferably bio-based polymers, inorganic precursors and polysaccharides with carboxylic acid groups are used to form the gel. Suitable bio-based polymers, inorganic precursors and polysaccharides with carboxylic acid groups are in principle known from the art. In particular, water-soluble biopolymers or biopolymers that form swollen dispersions in water are suitable. Suitable polysaccharides with carboxylic acid groups are, for example, alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches. The use of these bio-based polymers and polyionic biopolymers, such as polysaccharides and their derivatives, is particularly attractive due to their stability, availability, renewability and low toxicity. Inorganic precursors suitable in the context of the present invention must be soluble or at least partially soluble in the mixture (M1) and must solidify during the gelling process.

[0027] For the purposes of the present invention, a gel is a crosslinked system based on polymers that exists in contact with a liquid (known as a solvogel or lyogel) or with liquid water (aquagel or hydrogel), in which the polymer phase forms a continuous three-dimensional network.

[0028] In the context of the present invention, water-soluble means that the solubility in water is sufficient to form a solution that can be used to prepare a gel. In the context of the present invention, aqueous swollen dispersions can also be used to prepare a gel.

[0029] According to the invention, a gel is formed from the components of the mixture (M1) and at least one polyvalent metal ion. The components (C1) and (C2) used in the process of the invention must be suitable, in particular must have suitable functional groups, to allow the formation of a gel with the polyvalent metal ion.

[0030] Surprisingly, it has been found that the claimed method allows the production of aerogels that are prepared from harmless aqueous solutions, can be loaded with liquid or liquefied organic solvents or oils, exhibit little shrinkage when exposed to typical ambient conditions for storage stability, exhibit little shrinkage when loaded to maximize liquid capacity, are non-dusty, and do not require chemical treatments such as hydrophobization or covalent crosslinking. The resulting porous material exhibits little shrinkage in the dried aerogel form, so that the available volume remains large until loading of the aerogel is performed. Surprisingly, the method according to the invention allows the formation of round hydrogels, alcogels, and aerogel beads. The aerogel beads preferably exhibit less than 50% shrinkage when exposed to typical ambient conditions, and preferably less than 20% shrinkage when loaded with active ingredients or liquids. Preferably, the biopolymer is 100% biobased, and according to the invention, the aerogel does not require chemical crosslinking or hydrophobization.

[0031] Preferably, the porous material obtained by the method according to the invention is suitable for loading with liquid or liquefied organic solvents or oils and typically exhibits less than 60% shrinkage when exposed to humidity (60% rH, 48 h, 30° C.) as a dry aerogel and less than 50% shrinkage when loaded in the form of round beads with an average diameter of about 3 mm.

[0032] Surprisingly, it has been found that the claimed method allows the production of aerogels, e.g., aerogels based on bio-based polymers and inorganic precursors, and at least one polysaccharide having carboxylic acid groups, having low solids content and high surface area, preferably high pore volume and small pore size.

[0033] The properties of the aerogel can be customized by adjusting the composition of the mixture (M1), the reaction conditions at the stage of formation of the hydrogel (gel (A)), or the reaction conditions during the solvent exchange and drying stages. According to the invention, it is possible to influence the properties of the hydrogel and / or aerogel by varying the ratio of the components, controlling the parameters of step b) and also by introducing a wide range of organic and inorganic materials into the gel matrix.

[0034] According to the invention, at least one compound (C1) is used. Suitable bio-based polymers include, for example, bio-based phenolic polymers such as lignin and tannin. Suitable are, for example, proteins, in particular plant-based proteins, animal-based proteins, bacterial-based proteins, and fungal-based proteins, including yeast-based proteins from the food industry, for example, beer brewing. For example, cellulose, bacterial cellulose, modified cellulose, starch, sugars, chitosan, polyhydroxyalkanoates, whey protein isolate, potato protein isolate, starch protein isolate, gelatin, collagen, casein, or derivatives thereof, such as salts thereof, can be used according to the invention. Whey protein, pea protein, yeast protein and patatin are particularly suitable for preparing porous materials suitable as carrier materials.

[0035] According to a further embodiment, the present invention also relates to a method as described above, wherein compound (C1) is a protein, preferably a protein selected from the group consisting of whey protein, pea protein, yeast protein and patatin, in particular a protein selected from the group consisting of whey protein.

[0036] Inorganic precursors, such as silicates, titanates, vanadates, zirconates, aluminates, borates, ferrates, chromates, molybdates, tungstates, manganates, cobaltates, and also metal sulfides, oxides or carbides, can also be used as compound (C1) according to the invention.

[0037] According to a further embodiment, the present invention also relates to the method as described above, wherein compound (C1) is selected from the group consisting of water-soluble bio-based polyphenol polymers and silica.

[0038] According to the present invention, the water soluble bio-based polyphenol polymer is selected from the group consisting of lignin biopolymers and tannin biopolymers, and may in particular be selected from alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, biorefinery lignin, tannic acid, or tannins and tannin derivatives.

[0039] According to a further embodiment, the present invention also relates to the above method, wherein the water soluble biobased polyphenol polymer is selected from lignin biopolymers and tannin biopolymers, in particular alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, biorefinery lignin, tannic acid, or tannins and tannin derivatives.

[0040] According to the invention, mixtures of two or more biobased polymers or mixtures of one or more biobased polymers with metal oxides can also be used as compound (C1). For example, mixtures comprising one or more polymers selected from the group consisting of biobased polymers, such as lignin and tannins, cellulose, bacterial cellulose, modified cellulose, starch, sugars, chitosan, polyhydroxyalkanoates, whey protein isolates, potato protein isolates, starch protein isolates, yeast proteins, gelatin, collagen, casein or derivatives thereof, or mixtures comprising inorganic precursors and one or more polymers selected from the group consisting of biobased phenolic polymers, such as lignin and tannins, cellulose, bacterial cellulose, modified cellulose, starch, sugars, chitosan, polyhydroxyalkanoates, whey protein isolates, potato protein isolates, starch protein isolates, gelatin, collagen, casein or derivatives thereof, or pea proteins or yeast proteins can be used as component (C1).

[0041] According to the present invention, compound (C2) is preferably a polyanionic biopolymer, such as a polysaccharide. Compound (C2) may be selected from the group consisting of alginate, pectin, modified cellulose, xanthan, hyaluronic acid or modified starch. Thus, according to a further embodiment, the present invention also relates to the above-mentioned method, in which compound (C2) may be selected from the group consisting of alginate, pectin, modified cellulose, xanthan, hyaluronic acid or modified starch, preferably from the group consisting of alginate, pectin and modified cellulose, in particular from the group consisting of modified cellulose or from the group consisting of alginate.

[0042] According to a further embodiment, the present invention also relates to the method as described above, wherein compound (C2) is a polyanionic biopolymer, preferably a polyanionic biopolymer selected from the group consisting of alginates, pectins and modified celluloses.

[0043] According to the present invention, compound (C1) may be selected from the group consisting of, for example, lignin and tannin, also cellulose, bacterial cellulose, modified cellulose, starch, sugars, chitosan, polyhydroxyalkanoates, whey protein isolate, potato protein isolate, starch protein isolate, gelatin, collagen, casein or derivatives thereof, and silicates, titanates, vanadates, zirconates, aluminates, borates, ferrates, chromates, molybdates, tungstates, manganates, cobaltates and metal sulfides, metal oxides and metal carbides, and compound (C2) is an alginate. According to a further embodiment, compound (C1) may be, for example, a mixture comprising lignins and tannins, cellulose, bacterial cellulose, modified cellulose, starch, sugars, chitosan, polyhydroxyalkanoates, whey protein isolate, potato protein isolate, starch protein isolate, yeast protein, gelatin, collagen, casein or derivatives thereof, and a compound selected from the group consisting of silicates, titanates, vanadates, zirconates, aluminates, borates, ferrates, chromates, molybdates, tungstates, manganates, cobaltates and metal sulfides, metal oxides and metal carbides, and compound (C2) may be an alginate.

[0044] According to a further embodiment, compound (C1) is a protein, preferably a protein selected from the group consisting of whey protein, pea protein, yeast protein and patatin, and compound (C2) is selected from the group consisting of alginates, pectins and modified celluloses.

[0045] According to the present invention, the amounts of compounds (C1) and (C2) used in the process can vary, for example depending on the material properties to be achieved. A suitable amount of compound (C1) is, for example, in the range of 0.1% to 50% by weight based on the weight of mixture (M1), preferably in the range of 0.1% to 35% by weight based on the weight of mixture (M1), in particular in the range of 2.0% to 20% by weight based on the weight of mixture (M1).

[0046] According to a further embodiment, the present invention therefore also relates to the above-mentioned method, wherein mixture (M1) comprises compound (C1) in an amount of 0.1% by weight to 50% by weight, based on the weight of mixture (M1).

[0047] The ratio of compound (C1) to compound (C2) may also vary depending on the compounds used. Typically, mixture (M1) contains compound (C1) to compound (C2) in a ratio ranging from 55:45 to 98:2, preferably from 60:40 to 95:5.

[0048] According to a further embodiment, the present invention therefore also relates to a method as described above, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0049] In the context of the present invention, the pH value of the mixture (M1) may also vary depending on the compounds used. It has been found that advantageous results are obtained when the pH value of the mixture (M1) is in the range of 7 to 14, in particular in the range of 8 to 14 or 10 to 14, more preferably in the range of 11 to 14. The pH value of the mixture (M1) can be adjusted to improve the solubility of the polymer used.

[0050] According to a further embodiment, the present invention also relates to the above process, wherein the pH value of the mixture (M1) is in the range of 7-14.

[0051] In the method according to the present invention, according to step a), a mixture (M1) is provided. This mixture can be prepared by dissolving the desired amount of compounds (C1) and (C2) in, for example, distilled water. In the context of the present invention, it is also possible to adjust the pH value of the mixture to improve solubility.

[0052] According to step b), the mixture (M1) is contacted with an aqueous solution of polyvalent metal ions to prepare the gel (A).

[0053] The aqueous solution of the polyvalent metal ion can be prepared, for example, using a salt of the polyvalent metal ion.

[0054] According to the present invention, polyvalent metal ions are preferred which can form poorly soluble compounds with the polysaccharide compound (C2) having carboxylic acid groups and can form poorly soluble compounds with the compound (C1) used, i.e. act as bridging metal ions. Such polyvalent metal ions include, for example, alkaline earth metal ions and transition metal ions which form poorly soluble compounds with the polysaccharide having carboxylic acid groups. Alkaline earth metal ions, such as magnesium or calcium, are preferred. Calcium is particularly preferred. Also trivalent metal ions, such as aluminum or iron (III), are particularly preferred. Calcium salts are particularly preferred according to the present invention, since they are physiologically, particularly cosmetically acceptable, and have a stronger crosslinking and / or gelling effect compared to alginates. In addition, for example, beryllium, barium, strontium, zinc, cobalt, nickel, copper, manganese, iron, chromium, vanadium, titanium, zirconium, cadmium, molybdenum, tungsten, ruthenium, rhodium, iridium, palladium, platinum, and aluminum can also be used. According to the invention, mixtures of two or more polyvalent ions may also be used, for example mixtures containing divalent and trivalent ions, for example mixtures containing calcium and aluminum, mixtures containing calcium and ions.

[0055] The polyvalent metal ion is preferably added in the form of its salt.In principle, the corresponding anion can be selected arbitrarily.Preferably, chloride, acetate, nitrate, preferably calcium chloride, or salt of trivalent metal, such as iron(III) chloride, aluminum chloride or iron(III) nitrate, or mixtures thereof can be used.

[0056] The amount of the salt of the polyvalent metal ion is selected so that the concentration of the salt in the resulting solution is preferably in the range of about 1 to 20 mass%, preferably 1 to 10 mass%, particularly 1 to 5 mass%, and more preferably 1 to 3 mass%.

[0057] According to a further embodiment, the present invention also relates to the above method, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from alkaline earth metal ions.

[0058] According to a further embodiment, the present invention also relates to the above method, wherein the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions. Mixtures of polyvalent metal ions may also be used in accordance with the present invention.

[0059] The mixture (M1) provided in step (a) may also contain further salts, in particular such salts which do not form gels, and customary auxiliaries known to those skilled in the art as further components. Furthermore, the mixture (M1) may contain cosmetic or medical active substances, pharmaceutical agents, agricultural agents or food active substances.

[0060] Typically, the cosmetic or medical active substance, pharmaceutical agent, agricultural agent or food active substance remains at least partially in the gel or porous material under the conditions of the method according to the invention.

[0061] For example, water-soluble or water-dispersible materials are suitable.

[0062] Suitable substances may be selected, for example, from hyaluronic acid, collagen, keratin, silk fibroin, tannin, lignin (as antioxidant or sun protection factor), enzymes, polyvinylpyrrolidone (PVP), and povidone. Further suitable additives include whitening actives; free radical scavengers, UV absorbers, barrier lipids, peeling actives, retinoids, tanning actives, whitening agents, skin actives, chelating agents, flavonoids, moisturizing actives, exfoliating agents, anti-acne actives, anti-caking agents, anti-cellulite agents, anti-foaming agents, anti-fungal actives, anti-inflammatory actives, antimicrobial actives, antioxidants, antiperspirant / deodorant actives, anti-skin atrophy actives, antiviral agents, anti-wrinkle actives, artificial tanning agents and accelerators, astringents, barrier repair agents, binders, buffers, bulking agents, chelates, etc. The active ingredient may be selected from the group consisting of skin conditioners, colorants, dyes, enzymes, essential oils, film formers, fragrances, moisturizers, hydrocolloids, light diffusers, nail enamels, opacifying agents, optical brighteners, optical modifiers, particulates, fragrances, pH adjusters, preservatives, sequestrants, skin conditioners / moisturizers, skin feel improvers, skin protectants, skin sensates, skin treatment agents, skin exfoliants, skin lightening agents, skin soothing and / or healing agents, skin thickeners, sunscreen actives, topical anesthetics, vitamin compounds, and combinations thereof.

[0063] Suitable materials may be triglycerides, vegetable oils, vegetable oil derivatives, acetoglyceride esters, arcyl esters, arsenyl esters, lanolin and its derivatives, wax esters, beeswax derivatives, sterols and phospholipids, and combinations thereof; hydrocarbon oils and waxes or silicone oils, and combinations thereof.

[0064] The suitable substance may also be a pharmaceutical composition containing one or more pharmaceutical agents, preferably for oral administration. The one or more pharmaceutical agents are selected from therapeutic and diagnostic agents. Examples of suitable therapeutic agents include drugs acting on synaptic sites and neuroactive agent junctions; general and local analgesics; hypnotics and sedatives; drugs for the treatment of psychiatric disorders such as depression and schizophrenia; antiepileptics and anticonvulsants; drugs for the treatment of Parkinson's and Huntington's diseases, aging and Alzheimer's disease; excitatory amino acid antagonists, neurotrophic factors and neuroregenerative agents; trophic factors; drugs intended for the treatment of central nervous system trauma or stroke; drugs for the treatment of addiction and drug abuse; antiobesity drugs; antagonists and anti-inflammatory drugs; chemotherapeutic agents for parasitic infections and microbial diseases; immunosuppressants and anticancer drugs; hormones and hormone antagonists; heavy metals and heavy metal antagonists; non-metal toxic drugs. Examples of suitable diagnostic agents include, but are not limited to, antagonists of drugs, cell activators for cancer therapy, diagnostic materials for use in nuclear medicine, immunoactive and immunoreactive drugs, transmitters and their respective receptor agonists and receptor antagonists, their respective precursors and metabolites, transporter inhibitors, antibiotics, antispasmodics, antihistamines, antiemetics, relaxants, stimulants, sense and antisense oligonucleotides, encephalodilators, psychotropic drugs, antimanic drugs, vasodilators and constrictors, antihypertensive drugs, migraine medications, hypnotics, hyperglycemic and hypoglycemic drugs, antiasthmatic drugs, antiviral drugs, preferably anti-HIV drugs, genetic materials suitable for DNA, Si-RNA or antisense treatment of disease, and mixtures thereof. Examples of suitable diagnostic agents include, but are not limited to, diagnostic agents useful for diagnosis in nuclear medicine and radiotherapy.

[0065] Suitable materials may also be perfumes or perfume compositions that typically remain at least partially in the gel or porous material under the conditions of the method according to the invention. The perfume may be any fragrant material or mixture of materials, including natural and synthetic materials, that provide a pleasant scent. In addition, the perfume may contain auxiliary materials, such as fixatives, extenders, stabilizers, and solvents. Examples of suitable perfumes include, but are not limited to, silicone oils, essential oils, absolutes, resinoids, resins, and synthetic perfume ingredients (including saturated and unsaturated compounds, aliphatic compounds, carbocyclic compounds, heterocyclic compounds), such as hydrocarbons, alcohols, aldehydes, ketones, ethers, acids, esters, acetals, ketals, nitrites. It should be recognized that certain perfumes may include additional ingredients that function, for example, as carriers, diluents, stabilizers, and the like. Exemplary additional ingredients include glycols and vegetable oils. Reference to perfume ingredients includes not only the perfume, but also any additional ingredients that are combined with the perfume to provide beneficial properties such as stability, viscosity, and the like. Examples of suitable fragrances or perfumes are described, for example, in US Pat. No. 5,234,610.

[0066] According to a further embodiment, the present invention also relates to the above-mentioned method, in which in step a) a compound (C) suitable for forming a gel is added to the mixture (M1). The compound (C) may be soluble or partially soluble in the mixture (M1). In the context of the present invention, it is also possible that the compound (C) is insoluble in the mixture (M1).

[0067] According to a further embodiment, the present invention also relates to the process as described above, wherein the water-insoluble solid (S) is contacted with the mixture (M1).

[0068] The solid (S) can be, for example, a porous material or foam, a support or a fibrous material. According to the invention, it is also possible for the mixture (M1) to be present in the pores of the solid (S).

[0069] According to a further embodiment, the present invention also relates to a method as described above, wherein a compound (C) selected from pigments, opacifiers, flame retardants, metals, metal particles, metal nanoparticles, metal fibers, metal meshes, metal oxides, metal oxide particles, metal oxide nanoparticles, metal oxide fibers, metal salts, catalytic metals, catalytic materials, metal carbide or metal sulfide particles or nanoparticles, silicon-based materials, silicon particles, silicon nanoparticles, semiconductor-based materials, semiconductor particles, semiconductor nanoparticles, semiconductor fibers, semiconductor meshes, carbon materials, carbon black, graphite nanoparticles, graphite fibers, graphite sheets, graphite meshes, graphene nanoparticles, graphene fibers, graphene sheets, graphene meshes, metal-organic frameworks, sulfur, inorganic and / or organic fillers, nucleating agents, stabilizers, thermal control components, surface-active substances, fibers and foam reinforcements is added to the mixture (M1).

[0070] According to step b) of the present invention, the mixture (M1) is contacted with an aqueous solution of polyvalent metal ions to prepare the gel (A). Suitable mixing steps are in principle known to the person skilled in the art. For example, it is possible to add the mixture (M1) dropwise to the aqueous solution of polyvalent metal ions. It is also possible to provide the mixture (M1) in the pores of a support material or in admixture with fibers before contacting it with the aqueous solution of polyvalent metal ions to prepare the gel (A). It is also possible to contact the mixture (M1) with the polyvalent metal ions in an emulsion or in a spray process.

[0071] Gelation is known per se to the person skilled in the art and is described, for example, in WO 2009 / 027310, page 21, line 19 to page 23, line 13.

[0072] Preferably, the conditions are adjusted so that the hydrogels, alcogels and / or aerogels exhibit a round shape. Preferably, step b) results in round beads with an average diameter in the range of 0.5-3 mm. Preferably, no cross-linking or hydrophobization by covalent chemical reactions takes place.

[0073] Preferably, the temperature and pressure of step b) are adjusted to conditions under which a gel is formed. Suitable temperatures are in the range of 5-40° C., preferably in the range of 15-35° C. According to a further embodiment, the present invention also relates to the above process, wherein step b) is carried out at a temperature in the range of 5-40° C.

[0074] The rate of formation of the insoluble gel can be controlled very accurately and easily by appropriate selection of the conditions of step b).

[0075] The gel (A) obtained in step b) is a gel containing water, i.e. a hydrogel. According to the present invention, in step c) of the method of the present invention, the gel (A) obtained in step b) is exposed to a water-miscible solvent (L) to obtain a gel (B).

[0076] However, it is also possible to use the hydrogel (A) obtained as an intermediate of the above-mentioned process as it is. Many uses of hydrogels are known. The hydrogel (A) is particularly homogeneous and can be used according to the invention to prepare particles, which can be subjected to further processing.

[0077] According to the invention, a water-miscible solvent (L) is used in step c). In the context of the present invention, water-miscible means that the solvent is at least partially miscible with water to allow the exchange of the solvent in the gel.

[0078] Solvent exchange is performed by directly immersing the gel in a new solvent (single-step) or by sequentially immersing it in different water-new solvent mixtures with increasing content of new solvent in the previous immersion step after a certain time (exchange frequency) (Robitzer et al., 2008, Langmuir, 24(21), 12547-12552). The solvent selected for the water replacement must meet the following requirements: not dissolving the gel structure, completely soluble in the previous solvent (water), and also acceptable for pharmaceutical production. Furthermore, if the method includes a step of supercritical drying, the solvent (L) is preferably at least partially miscible with the supercritical medium.

[0079] The solvent (L) can in principle be any suitable compound or mixture of compounds which is liquid under the temperature and pressure conditions of step c) and which fulfills the above requirements.

[0080] Possible solvents (L) include, for example, alcohols, ketones, aldehydes, alkylalkanoates, organic carbonates, amides such as formamide and N-methylpyrrolidone, sulfoxides such as dimethylsulfoxide, aliphatic and cycloaliphatic halogenated or non-halogenated hydrocarbons, halogenated or non-halogenated aromatic compounds, and fluorine-containing ethers. Mixtures of two or more of the abovementioned compounds are likewise possible.

[0081] In many cases, particularly suitable solvents (L) are obtained by using two or more completely miscible compounds selected from the abovementioned solvents.

[0082] Suitable solvents are especially alcohols and ketones, such as C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

[0083] According to a further embodiment, the present invention also relates to the process as described above, wherein the solvent (L) used in step c) is selected from the group consisting of C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

[0084] Alcohols such as methanol, ethanol, isopropanol, and ketones such as acetone, methyl ethyl ketone are particularly suitable.

[0085] The solvent exchange according to step b) can be carried out in one, two, three or multiple steps with varying solvent concentrations. According to a preferred embodiment, the gel (A) is successively immersed in ethanol / water mixtures having concentrations of, for example, 30, 60, 90 and 100% by weight, respectively, for 5 minutes to 12 hours, depending on the particle size and porosity.

[0086] In step c) a gel (B) is obtained. According to step d) of the method of the invention, the gel (B) obtained in step c) is dried.

[0087] The drying in step (d) is carried out in a known manner. Drying under supercritical conditions is preferred, preferably after replacing the solvent with CO2 or another solvent suitable for the purpose of supercritical drying. Such drying is known per se to the person skilled in the art. Supercritical conditions are characterized by temperatures and pressures at which CO2 or the solvent used to remove the gelling solvent is present in the supercritical state. This allows to reduce the shrinkage of the gel body when the solvent is removed.

[0088] In the context of the present invention, it is also possible to dry the gel obtained by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0089] According to one embodiment, drying of the gel obtained is preferably carried out by converting the solvent (L) into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the solvent (L). Drying is therefore preferably carried out by removing the solvent (L) present during the reaction, without prior replacement with further solvent.

[0090] Such methods are likewise known to the person skilled in the art and are described in WO 2009 / 027310, page 26, line 22 to page 28, line 36.

[0091] According to a further embodiment, the present invention also relates to a method as described above, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0092] According to a further embodiment, the present invention also relates to a method as described above, wherein the drying according to step d) is carried out under supercritical conditions.

[0093] The method may also include one or more further modification steps, such as a molding step, a compression step, a lamination step, a hydrophobization step, or a carbonization step, which may include fibers and / or adhesives and / or thermoplastic materials. For example, it is also possible to combine one or more of these steps, such as a post-drying step with a hydrophobization step.

[0094] According to a further embodiment, the present invention also relates to the above method, wherein the method comprises one or more further modification steps of the dried gel.

[0095] According to a further embodiment, the present invention also relates to the above method, wherein the modification step is selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0096] The present invention also relates to a porous material obtained or obtainable by the above process. The porous material of the present invention is preferably an aerogel, a xerogel or a cryogel.

[0097] For purposes of this invention, a xerogel is a porous material produced by a sol-gel process in which the liquid phase is removed from the gel by drying below the critical temperature and pressure of the liquid phase ("subcritical conditions"). An aerogel is a porous material produced by a sol-gel process in which the liquid phase is removed from the gel under supercritical conditions. A cryogel is a porous material produced by freezing the solvent in the gel and removing the solid solvent by sublimation at room temperature.

[0098] The above process results in porous materials with improved properties. The aerogels produced according to the process of the invention preferably have a low density, preferably between 200 and 800 m 2 / g. In addition, the specific surface area is 2.1 to 9.5 cm for pore diameters of less than 100 nm. 3 Pore ​​volumes in the range of 1 / g are preferably obtained.

[0099] Preferably, the resulting porous material exhibits less than 60% shrinkage when exposed to humidity (60% rH, 48 hours, 30°C) as a dry aerogel and less than 50% shrinkage when loaded in the form of round beads of 3 mm average diameter.

[0100] Furthermore, the present invention therefore relates to a porous material obtained or obtainable by the method for preparing a porous material as disclosed above. In particular, the present invention relates to a porous material obtained or obtainable by the method for preparing a porous material as disclosed above, in which the drying according to step d) is carried out under supercritical conditions.

[0101] The porous material according to the present invention preferably has a density of 0.005 to 1 g / cm 3 , preferably 0.01 to 0.5 g / cm 3 (determined in accordance with DIN 53420).

[0102] The average pore size is determined by scanning electron microscopy and subsequent image analysis using a statistically significant number of pores. Corresponding methods are known to those skilled in the art. A Nova 3000b Surface Area Analyzer from Quantachrome Instruments was used to characterize the porous structure of the aerogels. It uses nitrogen adsorption and desorption at a constant temperature of 77 K.

[0103] The volume average pore size of the porous material is preferably 1 micron or less. The volume average pore size of the porous material is particularly preferably 750 nm or less, very particularly preferably 500 nm or less, in particular 250 nm or less. The volume average pore size of the porous material can be, for example, in the range of 1 to 1000 nm, preferably in the range of 2 to 500 nm, in particular in the range of 3 to 250 nm, more preferably in the range of 5 to 100 nm, and in particular in the range of 10 to 50 nm.

[0104] The porous material obtainable according to the invention preferably has a porosity of at least 70% by volume, in particular 70-99% by volume, particularly preferably at least 80% by volume, very particularly preferably at least 85% by volume, in particular 85-95% by volume. Porosity in volume % means that a certain percentage of the total volume of the porous material contains pores. From the viewpoint of minimizing thermal conductivity, a very high porosity is usually desirable, but the mechanical properties and processability of the porous material impose an upper limit on the porosity.

[0105] According to a further embodiment, the present invention also relates to a porous material as described above, wherein the specific surface area of ​​the porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 200 and 800 m 2 / g range.

[0106] Surprisingly, it has been found according to the invention that it is possible to obtain materials with a very low content of volatile organic compounds, even if the starting materials used contain higher amounts of volatile organic compounds. For example, lignin often contains volatile organic compounds, such as guaiacol, due to its preparation process.

[0107] According to a further embodiment, the present invention therefore also relates to a porous material as described above, wherein the content of volatile organic compounds (VOC) in the porous material is less than 50% of the content of volatile organic compounds (VOC) in the starting material used in the method.

[0108] According to a further embodiment, the present invention also relates to a porous material as described above, wherein the porous material is in the form of beads, preferably having an average diameter in the range of 0.5 mm to 3 mm.

[0109] The porous material according to the invention can be loaded with liquid or liquefied organic solvents or oils and shows little shrinkage when exposed to typical ambient conditions for storage stability, while showing little shrinkage when loaded to maximize liquid capacity. The porous material according to the invention has little shrinkage in the dried aerogel form, so that the available volume remains large until loading of the aerogel occurs. The porous material according to the invention has excellent adsorption properties and excellent mechanical stability to allow loading of adsorbed substances and steady release under ambient conditions.

[0110] According to the invention, for example cosmetic or medical active substances or pharmaceutical agents or agricultural agents or food active substances or fragrances or fragrance compositions can be introduced during the above-mentioned preparation methods, which are then at least partially present in the porous material and can also be released under suitable conditions.

[0111] According to the invention, it is also possible to contact the porous material with a suitable liquid composition comprising the cosmetic or medical active substance or pharmaceutical or agricultural or food active substance or flavor or fragrance composition to be subsequently at least partially adsorbed. Preferably, the method comprises mixing the porous material with the liquid composition and allowing sufficient time for an effective amount of said composition to be adsorbed and / or absorbed into the porous material. The liquid composition may be a solution, preferably a concentrated solution. Suitable are, for example, solutions or dispersions comprising the cosmetic or medical active substance or pharmaceutical or agricultural or food active substance or flavor or fragrance composition and a suitable solvent. In the context of the present invention, it is also possible to use the liquid active substance as it is, without adding a solvent. The porous material comprising the adsorbed substance can then be separated from the remaining solution or dispersion. According to the present invention, it is also possible to release the adsorbed substance under suitable conditions.

[0112] The loading of the liquid composition depends on the density of the liquid, the density of the dry porous material, and the shrinkage of the dry porous material when loaded with the liquid composition. The loading of the liquid composition can be 60 g / g or less, preferably 50 g / g or less, more preferably 45 g / g or less, and 5 g / g or more, preferably 7 g / g or more.

[0113] According to a further aspect, the present invention relates to the use of a porous material as defined above, or of a porous material obtained or obtainable by a method as defined above, as a support material or adsorbent.

[0114] The porous material obtainable according to the present invention preferably has a high porosity and a low density.Furthermore, the porous material preferably has a small average pore size.The combination of the above-mentioned properties allows this material to be used as an insulating material in the field of thermal insulation, in particular as a building material in ventilated conditions, or for applications in refrigerators, temperature-controlled logistics, clothing or batteries.

[0115] The present invention also relates to the use of the porous material as described above or of the porous material obtained or obtainable according to the method as described above as an insulation material or for vacuum insulation panels. The insulation material is, for example, an insulation material used for the interior or exterior insulation of buildings. The porous material according to the invention can advantageously be used in insulation systems, for example composite materials.

[0116] Furthermore, the present invention relates to the use of the porous material according to the invention in battery applications, as electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in cosmetic applications, in biomedical applications, in pharmaceutical applications, in agricultural applications and for the manufacture of medical products, such as cosmetic applications including, for example, facial treatment products such as skin scrubs or cleansing, or protective products such as UV protection products or products containing antioxidants.

[0117] According to a further aspect, the present invention relates to a method of use of said porous material or of a porous material obtained or obtainable according to said method as thermal insulation, for cosmetic, biomedical or pharmaceutical applications. According to a further preferred aspect, the present invention relates to a method of use of said porous material or of a porous material obtained or obtainable according to said method as thermal insulation, as carrier material for loading and releasing of active agents, for electrode material in batteries, fuel cells or electrolysis, for catalysis, for capacitors, for home appliances, for building and construction applications, for consumer electronics applications, for temperature controlled logistics applications, for vacuum insulation applications, for batteries, for clothing applications, for food applications, for cosmetic applications, for biomedical applications, for agricultural applications, for consumer applications, for packaging applications or for pharmaceutical applications.

[0118] Preferred embodiments are described in the claims and in the specification. Combinations of preferred embodiments do not fall within the scope of the invention. Preferred embodiments of the components used are described below.

[0119] The present invention includes the following embodiments, including certain combinations of the embodiments as indicated by their respective interdependencies defined therein.

[0120] 1. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of water-soluble bio-based polymers and inorganic precursors, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0121] 2. The method of embodiment 1, wherein the compound (C1) is selected from the group consisting of water-soluble bio-based polyphenol polymers and silica.

[0122] 3. The method according to embodiment 1 or 2, wherein the mixture (M1) comprises compound (C1) in an amount ranging from 0.1% to 50% by weight, based on the weight of the mixture (M1).

[0123] 4. The method according to any one of the preceding embodiments, wherein the mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0124] 5. The method according to any one of the preceding claims, wherein the pH value of the mixture (M1) is in the range of 7 to 14, in particular 8 to 14.

[0125] 6. The method according to any one of the preceding claims, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0126] 7. The method according to any one of the preceding claims, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps being selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0127] 8. The method according to any one of the preceding embodiments, wherein the solvent (L) used in step c) is selected from the group consisting of C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

[0128] 9. The method according to any one of the preceding embodiments, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

[0129] 10. The method according to any one of the preceding claims, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control elements, fibers and foam reinforcements is added to the mixture (M1).

[0130] 11. The method according to any one of the preceding claims, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and pressure of the liquid contained in the gel.

[0131] 12. The method according to any one of the preceding claims, wherein the drying according to step d) is carried out under supercritical conditions.

[0132] 13. A porous material obtained or obtainable by the method according to any one of embodiments 1 to 12.

[0133] 14. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 200 and 800 m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 14. The porous material of embodiment 13, wherein the porous material has a viscosity in the range of 1 / g.

[0134] 15. The porous material according to embodiment 13 or 14, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the starting material used in the method.

[0135] 16. Use of the porous material according to any one of embodiments 13 to 15 or the porous material obtained or obtainable by the method according to any one of embodiments 1 to 12 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0136] 17. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of water-soluble biobased polyphenol polymers and silica, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0137] 18. The method according to embodiment 17, wherein compound (C1) is selected from the group consisting of lignin biopolymers and silica.

[0138] 19. The method according to embodiment 17 or 18, wherein mixture (M1) comprises compound (C1) in an amount of 0.1% to 50% by weight, based on the weight of mixture (M1).

[0139] 20. The method according to any one of embodiments 17 to 19, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0140] 21. The method according to any one of embodiments 17 to 20, wherein the pH value of the mixture (M1) is in the range of 7 to 14, in particular 8 to 14.

[0141] 22. The method according to any one of embodiments 17 to 21, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0142] 23. The method according to any one of embodiments 17 to 22, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps being selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0143] 24. The method according to any one of embodiments 17 to 23, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0144] 25. The method according to any one of embodiments 17 to 24, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

[0145] 26. The method according to any one of embodiments 17 to 25, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

[0146] 27. The method according to any one of embodiments 17 to 26, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0147] 28. The method according to any one of embodiments 17 to 26, wherein the drying according to step d) is carried out under supercritical conditions.

[0148] 29. A porous material obtained or obtainable by the method according to any one of embodiments 17 to 28.

[0149] 30. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 200 and 800 m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 30. The porous material of embodiment 29, wherein the porous material has a viscosity in the range of 1 / g.

[0150] 31. The porous material according to embodiment 29 or 30, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the starting material used in the method.

[0151] 32. Use of the porous material according to any one of embodiments 29 to 31 or obtained or obtainable by the method according to any one of embodiments 17 to 28 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0152] 33. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of water-soluble lignin biopolymers and silica, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: The method, wherein the compound (C2) is selected from the group consisting of alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches.

[0153] 34. The method of embodiment 33, wherein the compound (C2) is selected from the group consisting of alginates.

[0154] 35. The method according to embodiment 33 or 34, wherein mixture (M1) comprises compound (C1) in an amount of 0.1% to 50% by weight, based on the weight of mixture (M1).

[0155] 36. The method according to any one of embodiments 33 to 35, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0156] 37. The method according to any one of embodiments 33 to 36, wherein the pH value of the mixture (M1) is in the range of 7 to 14 or 8 to 14.

[0157] 38. The method according to any one of embodiments 33 to 37, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0158] 39. The method according to any one of embodiments 33 to 38, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps being selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0159] 40. The method according to any one of embodiments 33 to 39, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0160] 41. The method according to any one of embodiments 33 to 40, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

[0161] 42. The method according to any one of embodiments 33 to 41, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

[0162] 43. The method according to any one of embodiments 33 to 42, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0163] 44. The method according to any one of embodiments 33 to 42, wherein the drying according to step d) is carried out under supercritical conditions.

[0164] 45. A porous material obtained or obtainable by the method according to any one of embodiments 33 to 44.

[0165] 46. ​​The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 200 and 800 m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 46. ​​The porous material of embodiment 45, wherein the porous material has a viscosity in the range of 1 / g.

[0166] 47. The porous material of embodiment 45 or 46, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the starting material used in the method.

[0167] 48. Use of the porous material according to any one of embodiments 45 to 47 or the porous material obtained or obtainable by the method according to any one of embodiments 33 to 44 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0168] 49. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of lignin biopolymers and silica, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of divalent or trivalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: The method, wherein the compound (C2) is selected from the group consisting of alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches.

[0169] 50. At least the following steps: a) providing a mixture (M1) comprising water, at least one compound (C1) selected from the group consisting of lignin biopolymers and silica, and at least one component (C2) selected from the group consisting of alginates; b) contacting the mixture (M1) with an aqueous solution of divalent or trivalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0170] 51. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0171] 52. The method according to embodiment 51, wherein compound (C1) is a protein, preferably a protein selected from the group consisting of whey protein, pea protein, yeast protein and patatin, in particular from the group consisting of whey protein.

[0172] 53. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: 13. The process according to claim 12, wherein the compound (C1) is a protein, preferably a protein selected from the group consisting of whey protein, pea protein, yeast protein and patatin, in particular from the group consisting of whey protein.

[0173] 54. The method according to any one of embodiments 51 to 53, wherein compound (C2) is a polyionic biopolymer, preferably a polyionic biopolymer selected from the group consisting of alginates, pectins and modified celluloses.

[0174] 55. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: 1. A process according to claim 1, wherein compound (C1) is a protein, preferably a protein selected from the group consisting of whey protein, pea protein, yeast protein and patatin, in particular from the group consisting of whey protein, and compound (C2) is a polyionic biopolymer, preferably a polyionic biopolymer selected from the group consisting of alginates, pectins and modified celluloses.

[0175] 56. The method according to any one of embodiments 51 to 55, wherein mixture (M1) comprises compound (C1) in an amount ranging from 0.1% by weight to 50% by weight, based on the weight of mixture (M1).

[0176] 57. The method according to any one of embodiments 51 to 56, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0177] 58. The method according to any one of embodiments 51 to 57, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps being selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0178] 59. The method according to any one of embodiments 51 to 58, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0179] 60. The method according to any one of embodiments 51 to 59, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

[0180] 61. The method according to any one of embodiments 51 to 60, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

[0181] 62. A porous material obtained or obtainable by the method according to any one of embodiments 51 to 61.

[0182] 63. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); 2. A porous material obtained or obtainable by a process comprising:

[0183] 64. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A porous material obtained or obtainable by a process comprising: 1. A porous material, wherein compound (C1) is a protein, preferably a protein selected from the group consisting of whey protein, pea protein, yeast protein and patatin, in particular from the group consisting of whey protein, and compound (C2) is a polyionic biopolymer, preferably a polyionic biopolymer selected from the group consisting of alginates, pectins and modified celluloses.

[0184] 65. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 200 and 800 m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 65. The porous material of any one of embodiments 62 to 64, wherein the molecular weight is in the range of 1 / g.

[0185] 66. A porous material according to any one of embodiments 60 to 65, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the starting material used in the method.

[0186] 67. A porous material according to any one of embodiments 62 to 66, wherein the porous material is in the form of beads, preferably having an average diameter in the range of 0.5 mm to 3 mm.

[0187] 68. Use of a porous material according to any one of embodiments 62 to 67 or obtained or obtainable by the method according to any one of embodiments 51 to 61 as a support material or adsorbent.

[0188] 69. Use of the porous material according to any one of embodiments 62 to 67 or the porous material obtained or obtainable by the method according to any one of embodiments 51 to 61 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in household and commercial appliance applications, in temperature control logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0189] The present invention will now be described with reference to examples. EXAMPLES

[0190] 1. Preparation Example Ingredients: Kraft lignin (UPM), Sodium hydroxide (NaOH, Sigma Aldrich), Calcium chloride (CaCl2, Sigma Aldrich), Pure ethanol (Carl Roth), Sodium alginate (Hydagen, BASF), Hexamethyldisilazane (HMDZ, Sigma Aldrich), Ludox SM30 (Sigma Aldrich), Whey protein (Agropure Ingredients), Xanthan (Sigma Aldrich), Microcrystalline cellulose (MCC, Sigma Aldrich), Sodium caseinate (Sigma Aldrich), Tannic acid (Sigma Aldrich), Potato starch (Sigma Aldrich), Gelatin (Sigma Aldrich), Pea protein isolate (Elmsland group), Potato protein isolate (Avebe), Augeo (Solvay).

[0191] 1.1 Whey protein / alginate hybrid aerogel Solution 1: Whey protein was dissolved in water at room temperature to a concentration of 20% by weight.

[0192] Solution 2: Sodium alginate was dissolved in water at room temperature to a concentration of 20% by weight.

[0193] Solution 3: A CaCl2 aqueous solution (20 g / L) was prepared at room temperature.

[0194] Solutions 1 and 2 were combined at a whey protein to sodium alginate mass ratio of 95:5 and a total concentration of 15% by mass. The pH was adjusted to ∼7 with NaOH to obtain solution 4.

[0195] Solution 4 was added dropwise to solution 3 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 3.

[0196] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0197] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain hybrid whey protein / alginate aerogel particles.

[0198] The bulk density of the aerogel particles was ~150 g / l.

[0199] The surface area of ​​the determined aerogel particles is 139 m 2 / g.

[0200] 1.2 Hybrid aerogels with various biopolymers Solution 1: Microcrystalline cellulose, sodium caseinate, tannic acid, potato starch or gelatin were mixed with 2% by weight aqueous sodium alginate to obtain various solutions with concentrations and weight ratios as shown in Table 2. For potato starch, the potato starch was heated to 90°C before mixing for dissolution. For gelatin, the gelatin dispersion was heated to 80°C before mixing for dissolution. For microcrystalline cellulose (MCC), 6g MCC was added to 94g 8% by weight NaOH with stirring at -8°C and the resulting mixture was left at 4°C for 24 hours. 40% by weight NaOH was added to each solution until the pH shown in Table 2 was obtained.

[0201] Solution 2: An aqueous CaCl2 solution (10 g / L) was prepared at room temperature and adjusted to a pH of 10 with 1 M NaOH.

[0202] Solution 1 was added dropwise to solution 1 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 2.

[0203] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0204] The alcogel particles were dried using supercritical carbon dioxide at 60° C. and 120 bar for 1 hour to obtain hydrophilic hybrid aerogel particles having the bulk density and surface area shown in Table 2.

[0205] For hydrophobization, 50 ml of hydrophilic aerogel particles were placed in a filter bag and placed in a 2 liter reactor. 50 ml of HMDZ was also placed in a small open container and placed in the reactor. The reactor was closed and heated to 115°C. After 20 hours, the reactor was cooled to room temperature and hydrophobic aerogel particles with the surface areas shown in Table 1 were removed from the reactor.

[0206] [Table 1]

[0207] 2. Preparation of Hybrid Aerogels Using a blender, biopolymer A and biopolymer B were dissolved in water in the target ratio and mass concentration shown in Table 1. Using a syringe needle connected to a pump and reservoir, the resulting solution was dripped into a double volume of 50 g / l polyvalent metal salt solution at room temperature to obtain hydrogel beads (the diameter of the syringe needle was adjusted to a hydrogel particle size d of 2 mm). The resulting hydrogel beads were cured in a gelling bath at room temperature for 2 h. The shape of the hydrogel beads was qualitatively evaluated for roundness and gel integrity. The diameter d0 of 10 hydrogel beads was measured and the average value was taken. The hydrogel beads were washed with water and the water was exchanged successively in three steps with >98% ethanol to obtain alcogel beads. The alcogel beads were dried using supercritical CO2 to obtain aerogel beads. The diameter d of 10 aerogel beads was measured. e The values ​​were measured and averaged to calculate the shrinkage rate.

[0208] The beads were tested for stability and loading and the results are shown in Tables 2a and 2b.

[0209] [Table 2]

[0210] [Table 3]

[0211] 3. Methods Used 3.1 The pore volume was measured using a Nova 4000e pore size analyzer from Quantachrome Instruments according to DIN 66134:1998-02. Approximately 15-20 mg of sample was divided from the original sample and placed in a measuring glass cell. The sample was degassed at 60°C under a vacuum of 50 mm Hg for 15 hours to remove any adsorbed components on the sample. The mass of the sample was measured again before analyzing the surface area and pore size.

[0212] 3.2 Surface area measurements: The specific surface area was measured by the Brunauer-Emmet-Teller (BET) method using low-temperature nitrogen adsorption analysis (at the boiling point of nitrogen, 77 K) in the P / P0 range recommended by IUPAC (0.05-0.30). A graph of 1 / ((w.(P0 / P-1))) versus P / P0 gave a linear plot with a correlation coefficient (r) of more than 0.999.

[0213] 3.3 Humidity test: 5 ml of aerogel beads were placed in a Petri dish. The diameter d0 of 10 aerogel beads was measured and the average value was taken. The aerogel beads were exposed to 30°C and 60% relative humidity for 48 hours. The diameter d0 of 10 aerogel beads was measured and the average value was taken. e The values ​​were measured and averaged to calculate the shrinkage rate.

[0214] 3.4 Liquid Loading: 5 ml of aerogel beads were placed in a glass vial. The diameter d0 of 10 beads was measured and the average value was taken. Three to four drops of liquid or liquefied organic solvent or oil were added to the beads, gently stirring the beads after every few drops to distribute the active substance, and the addition was stopped as soon as a supernatant liquid was observed. The diameter d0 of 10 loaded beads was measured and the average value was taken. e The mechanical elasticity was evaluated by compressing the sample with two fingers.

[0215] The shrinkage rate is S=(d e -d0) / d0, where d0 is the initial bead diameter and d e is the final bead diameter.

[0216] References: Journal of Supercritical Fluids,2015,105,1-8 US20190329208A1 Grishechko, L. et al., Industrial Crops and Products, 2013, 41, 347~355 Partap et al. (2006, “Supercritical Carbon Dioxide in Water” Emulsion-Templated Synthesis of Porous Calcium Alginate Hydrogels. Advanced Materials 18,501-50 WO 2016032733A2 WO 2019167013A1 EP 3741794A1 EP 2663395B1 CN 114958480A WO 2018056652A WO 2017023702A1 Budtova et al. (Cellulose 2019,26,81-121(10.1007 / s10570-018-2189-1) CN 105601983B WO 2019190379A1 WO 96 / 25950 A1 WO 9501165A1 WO 2009062975A1 WO 02051389A2 WO 2009 / 027310 Robitzerら,2008,Langmuir,24(21),12547~12552

Claims

1. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of bio-based polymers, at least one polyionic biopolymer as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

2. 2. The method according to claim 1, wherein the compound (C1) is a protein, preferably a protein selected from the group consisting of whey proteins, pea proteins, yeast proteins and patatin, in particular from the group consisting of whey proteins.

3. 3. The method according to claim 1 or 2, wherein the compound (C2) is a polyionic biopolymer, preferably a polyionic biopolymer selected from the group consisting of alginates, pectins and modified celluloses.

4. 3. The method according to claim 1, wherein the mixture (M1) comprises the compound (C1) in an amount of 0.1% by weight to 50% by weight, based on the weight of the mixture (M1).

5. The method according to claim 1 or 2, wherein the mixture (M1) comprises the compound (C1) and the compound (C2) in a ratio ranging from 55:45 to 98:

2.

6. 3. The method according to claim 1 or 2, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps are selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step and a carbonization step.

7. 3. The process according to claim 1 or 2, wherein the solvent (L) used in step c) is selected from the group consisting of C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

8. 3. The process according to claim 1 or 2, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

9. 3. The method according to claim 1 or 2, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surfactants, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

10. 2. A porous material obtained or obtainable by the method of claim 1.

11. The specific surface area of ​​the porous material is determined using the BET theory in accordance with DIN 66134:1998-0 and is in the range of 200 to 800 m 2 / g and the pore volume is in the range of 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 The porous material according to claim 10, wherein the molecular weight is in the range of 1 / g.

12. 11. The porous material of claim 10, wherein the content of volatile organic compounds (VOC) in the porous material is less than 50% of the content of volatile organic compounds (VOC) in the starting material used in the method.

13. The porous material according to claim 10, wherein the porous material is in the form of beads, preferably having an average diameter in the range of 0.5 mm to 3 mm.

14. 11. Use of a porous material according to claim 10 or obtained or obtainable by the method according to claim 1 as a support material or adsorbent.

15. 11. Use of the porous material according to claim 10 or obtained or obtainable by the method according to claim 1 as a thermal insulation material, as a carrier material for loading and releasing of active agents, in battery applications, in electrode materials in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in domestic and commercial appliance applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

Citation Information

Patent Citations

  • A natural polysaccharide aerogel, its preparation method and its application in cigarettes

    CN105601983B

  • Preparation method of aerogel-based slow-release essence

    CN114958480A

  • Hydrophobic and hydrophilic aerogels encapsulated with peg hydrogel via surface initiated photopolymerization

    EP2663395B1

  • Aerogel having active material loaded therein, and complex of aerogel and hydrogel

    EP3741794A1

  • US02010329208A1